2015
DOI: 10.1364/oe.23.023035
|View full text |Cite
|
Sign up to set email alerts
|

High-speed adaptive optics for imaging of the living human eye

Abstract: Abstract:The discovery of high frequency temporal fluctuation of human ocular wave aberration dictates the necessity of high speed adaptive optics (AO) correction for high resolution retinal imaging. We present a high speed AO system for an experimental adaptive optics scanning laser ophthalmoscope (AOSLO). We developed a custom high speed ShackHartmann wavefront sensor and maximized the wavefront detection speed based upon a trade-off among the wavefront spatial sampling density, the dynamic range, and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…3 , right), suggesting that a loop rate between 10 and 40 corrections per second would cancel them (assuming typical latencies and gain) and achieve closed-loop performance near the diffraction limit (Strehl ratio > 0.8). 30 Later, aberration bandwidths of 30 Hz 31 33 or higher 34 were observed, suggesting that substantially higher rates may be beneficial. A recent study using a rate of 110 corrections per second demonstrated the predicted improvements in resolution and contrast.…”
Section: Improving Transverse Resolution With Adaptive Opticsmentioning
confidence: 98%
See 1 more Smart Citation
“…3 , right), suggesting that a loop rate between 10 and 40 corrections per second would cancel them (assuming typical latencies and gain) and achieve closed-loop performance near the diffraction limit (Strehl ratio > 0.8). 30 Later, aberration bandwidths of 30 Hz 31 33 or higher 34 were observed, suggesting that substantially higher rates may be beneficial. A recent study using a rate of 110 corrections per second demonstrated the predicted improvements in resolution and contrast.…”
Section: Improving Transverse Resolution With Adaptive Opticsmentioning
confidence: 98%
“…A recent study using a rate of 110 corrections per second demonstrated the predicted improvements in resolution and contrast. 33 …”
Section: Improving Transverse Resolution With Adaptive Opticsmentioning
confidence: 99%
“…Across all of these applications, there is a distinct benefit to scanning at high speeds as it translates to higher throughput for optical targeting and actuation, for the acquisition of sensing and recording data, and for the processing of materials into desired products. 2,7 Despite the ubiquity of optical scanning across disciplines, specific embodiments of 3D scanning tools vary widely and in accordance with the diversity in performance needs across applications. Two important specifications driving this variety are the lateral (XY) and axial (Z) dimensions of both the whole volume and elemental pattern of interest.…”
Section: D Optical Scanningmentioning
confidence: 99%
“…First, wavefront sensing and adaptive optics can improve the spot size of the beam on the retina and account for aberrations in the eye. Such systems have been reported for human retinal OCT and scanning laser ophthalmoscope systems [27,28] and for murine retinal OCT systems [29,30]. Classically, these OCT systems employ a wavefront sensor (either with a Shack-Hartmann wavefront sensor or computationally).…”
Section: Corneal Contactmentioning
confidence: 99%